2005
DOI: 10.1097/01.brs.0000160842.43482.cd
|View full text |Cite
|
Sign up to set email alerts
|

Adult Scoliosis: Prevalence, SF-36, and Nutritional Parameters in an Elderly Volunteer Population

Abstract: Previous reports note a prevalence of adult scoliosis up to 32%. In this study, results indicate a scoliosis rate of 68% in a healthy adult population, with an average age of 70.5 years. This study found no significant correlations between adult scoliosis and visual analog scale scores or nutritional status in healthy, elderly volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
374
0
19

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 762 publications
(419 citation statements)
references
References 8 publications
5
374
0
19
Order By: Relevance
“…Adult scoliosis (de novo scoliosis in adults): Scoliosis has a prevalence of more than 8 % in adults over the age of 25 and rises up 68 % in the age of over 60 years, caused by degenerative changes in the aging spine [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Adult scoliosis (de novo scoliosis in adults): Scoliosis has a prevalence of more than 8 % in adults over the age of 25 and rises up 68 % in the age of over 60 years, caused by degenerative changes in the aging spine [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported prevalence rates of 8.3, 8.9, and 13.3 % for adult scoliosis [16][17][18]. There is sufficient evidence to assume that the growing elderly population will result in an increase in prevalence rates of adult scoliosis [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the aging population, ASD causes a very high level of functional disability due to severe back and leg pain, subsequently reducing overall quality of life [1]. The prevalence of such curvatures of the spine has been reported being as high as 68% in healthy volunteers over the age of 60 [2][3][4]. It is expected that with the growing elderly population an increase in prevalence and incidence rates of symptomatic ASD will be seen [5,6].…”
Section: Introductionmentioning
confidence: 99%